2012
DOI: 10.1108/02634501211226285
|View full text |Cite
|
Sign up to set email alerts
|

Can after sale service generate brand equity?

Abstract: PurposeThis research attempts to empirically expand the Aaker's consumer based brand equity model in hybrid business firms by incorporating after sales service as a new dimension. Exploring and understanding the drivers of consumer based brand equity in a hybrid business context will help in building industry specific competitive barriers and generating brand wealth.Design/methodology/approachThe data were collected from Pakistani adults using a structured questionnaire based on established scales. Convenience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 66 publications
0
28
0
Order By: Relevance
“…Therefore, the data collected from the most representative-data across all the possible spectrum of the whole region -geographical areas, professions, sections of the society and gender within the brand loyalty) as the reflective constructs to measure the brand equity. In the same line, Ahmed and Butt (2012) have used indirect approach to measure Customer based brand equity by employing multiple reflective indicators. Furthermore, the other relevant constructs of the brand equity including attitude and purchase intention (Fornell andBookstein, 1982, Jarvis et al, 2003) and brand preferences (Rajagopal, 2010) Following is the goodness of fit criteria used for evaluating the goodness of fit of the model;…”
Section: Two Political Parties Of Pakistan Pakistan Muslim League (Nmentioning
confidence: 99%
“…Therefore, the data collected from the most representative-data across all the possible spectrum of the whole region -geographical areas, professions, sections of the society and gender within the brand loyalty) as the reflective constructs to measure the brand equity. In the same line, Ahmed and Butt (2012) have used indirect approach to measure Customer based brand equity by employing multiple reflective indicators. Furthermore, the other relevant constructs of the brand equity including attitude and purchase intention (Fornell andBookstein, 1982, Jarvis et al, 2003) and brand preferences (Rajagopal, 2010) Following is the goodness of fit criteria used for evaluating the goodness of fit of the model;…”
Section: Two Political Parties Of Pakistan Pakistan Muslim League (Nmentioning
confidence: 99%
“…It is apparent that the car brand quality and the level of service delivered to customer s are principally two different concepts (Ahmad & Butt, 2012). Nevertheless, the importance of after-sales as a main pillar of competitive advantage and business opportunity requires a transition from the conventional productorientation to customer-orientation, where the after-sales service plays the role as it is the main costumer voice.…”
Section: Resultsmentioning
confidence: 99%
“…Automobile sector operates on a hybrid model which makes it dependent on authorized dealers providing assistance through sales and after sales service. Previous research has suggested that authorized dealers providing sales assistance and after sales service in automobile sector play a critical role in branding (Ahmad & Butt, 2012). After sales service is also found to enhance the perception of a brand and can be used as a tool to counter competition (Asugman et al, 1997;Rigopoulou et al, 2008).…”
Section: Hypotheses Development and Conceptual Model After Sales Servmentioning
confidence: 99%
“…After sales service is also found to enhance the perception of a brand and can be used as a tool to counter competition (Asugman et al, 1997;Rigopoulou et al, 2008). Research has also shown that the knowledge of a brand depends on the availability of after sales service for the customers (Ehinlanwo & Zairi, 1996), and the after sales service is also found to influence brand equity (Eagle et al, 2003;Ahmad & Butt, 2012). Thus the following hypothesis is formulated: H1: After sales service has a positive effect on brand equity.…”
Section: Hypotheses Development and Conceptual Model After Sales Servmentioning
confidence: 99%